Kisah Exodus Bani Israil sebagai Titik Temu Terhadap Perspektif Umat Beragama untuk Jalan Damai - Suriawan Surna; Aji Suseno; Paul Kristiyono (Sekolah Tinggi Teologi Kadesi Bogor, 2021)
It is undeniable that the Israeli-Palestinian conflict has the potential to create chaos in relations between Christians and Muslims at the grassroots level. The perspective from a religious point of view often complicates the Israeli-Palestinian conflict. It must be realized, however, that from a religious perspective there is a meeting point between Islam and Christianity so as to prevent conflict among religious communities. The meeting point of the Islamic and Christian viewpoints can be based on the story of the exodus or the release of the Israelites or the Hebrews from slavery in the land of Egypt which is written in the Bible and the Koran. Exodus (the liberation of the people of Israel from slavery in Egypt) can be a meeting point for Christians and Muslims in Indonesia to establish a dialogue that respects and appreciates each other in good relations between the two religious communities, and further provides an understanding that religious perspectives can be combined with the principles of international relations to achieve peace between Israel and Palestine within the framework of a two-state solution as championed by the Indonesian government internationally.